The world's end - Robertson, David, 1977- (Robertson, David, 1977- Misewa saga, 2025)
"Eli must embrace his unique heritage and make an impossible decision about his future, and the future of Misewa, in this thrilling last adventure in the award-winning, Narnia-inspired Indigenous middle-grade fantasy series. Eli, Morgan and Emily manage to free themselves from captivity as the battle between the humans, animal beings, and Bird Warriors rages on. But there's another, more personal battle, as Eli and an unlikely ally fight to save Mahihkan's life through a previously forbidden portal. When the Sleeping Giant rumbles to life, the stakes hit an all-time high, and Eli has to reach deep within himself to summon the power so that he can protect Misewa against the dangers of colonization . . . forever."--